A study on the potential for rationalizing road public transport services with respect to the LRT Line 2 Extension - Belizario, Maria Celline I.; Dela Paz, Gio Carlo S.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The main purpose of the study is to analyze the current transport conditions along the LRT Line 2 Extension, focusing on public transport services that may need to be rationalized with respect to the currently under construction, LRT Line 2 Extension from Santolan to Emerald and Masinag. Once the Line 2 Extension is operational, there will be a direct competition between it and the current road public transport services along the study area such as jeepneys and UV Express franchise. This leads to the possibility of rationalizing the road public transport services. To do this, the data on the drivers' perspective about the construction of the Line 2 Extension is collected through surveys, recording travel time by riding the jeepneys and UV Express, and data on the process of route modification process regulated by the LTFRB. Using the data from the survey, the drivers' choice on new route designations is recorded. The travel time recorded for each route is used to determine the average speed for each road. The data is iterated to represent all possible combinations of road segments and based on the average speed, which should be as high as possible, the new proposed routes were made.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Route surveying; Local transit -- Philippines